Analisis Variabel yang Mempengaruhi Kepuasan Pemilihan Moda Transportasi Online di Kota Palangka Raya - KARIN MELINDA WIBOWO (Universitas Lambung Mangkurat, 2025)
Everyone needs transportation to fulfill their living needs, such as for work, school, recreation and social interaction. Travel to various places in Palangka Raya City with online transportation modes such as Gojek and Grab. For the choice of transportation mode, travelers consider various factors such as comfort, cost, security, affordability, regularity, waiting time for departure and length of travel time. In this study, data collection was obtained from questionnaires and respondents who considered the respondent's education, the number of two-wheeled vehicles owned, the costs incurred for transportation, and the income of each respondent, as well as the purpose of each respondent's travel. From the results of the questionnaire that has been distributed, a descriptive analysis is then carried out to determine which variable is superior in the selection of online transportation mode by respondents. The results obtained showed that respondents chose to strongly agree on the selection of online transportation mode by considering several superior variables, namely Comfort Level (X1) with a percentage of 68.3%, Safety Level (X3) with a percentage of 62.5%, Safety Level with a percentage of 59.2%. For the Agree option, respondents chose several variables, namely Regularity Level (X5) with a percentage of 36.7%, Affordableness Level (X6) with a percentage of 41.7% and Travel Time Length (X7) with a percentage of 43.3%, who chose Gojek and Grab as the chosen Online Transportation.